AIR POLLUTION IN TASHKENT CITY AND ITS IMPACT ON THE “GREEN ECONOMY” (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the current state of air pollution in the city of Tashkent and its impact on the transition to a “green economy.” Global climate change and declining air quality are becoming serious challenges for major cities in the context of urbanization. The author identifies the main causes of this situation, including the intensity of vehicle traffic, the use of low-quality fuel, the reduction of green zones, and the lack of effective environmental control. The research proposes strategic measures to combat air contamination and stresses the importance of political will and a systemic approach in their implementation.